2012
DOI: 10.1186/1471-2288-12-93
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of extensive recruitment effort persist during follow-ups and are consistent across age group and survey method. The TRAILS study

Abstract: BackgroundExtensive recruitment effort at baseline increases representativeness of study populations by decreasing non-response and associated bias. First, it is not known to what extent increased attrition occurs during subsequent measurement waves among subjects who were hard-to-recruit at baseline and what characteristics the hard-to-recruit dropouts have compared to the hard-to-recruit retainers. Second, it is unknown whether characteristics of hard-to-recruit responders in a prospective population based c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 41 publications
0
73
0
Order By: Relevance
“…Of the baseline participants, 2149 children participated in the second wave (96.4%, 13.5 years, SD 0.53), 1816 in the third wave (81.4%, 16.3 years, SD 0.69) and 1881 in the fourth wave (84.3% of baseline, mean age 19 years, SD 0.58). At baseline, no differences in psychopathology between respondents and non-respondents were observed;16 also during follow-up no differences in psychopathology between those retained and those who dropped out were found 18. More detailed information about design, sample, procedures and non-response analysis of the TRAILS study can be found elsewhere 16 17.…”
Section: Methodsmentioning
confidence: 99%
“…Of the baseline participants, 2149 children participated in the second wave (96.4%, 13.5 years, SD 0.53), 1816 in the third wave (81.4%, 16.3 years, SD 0.69) and 1881 in the fourth wave (84.3% of baseline, mean age 19 years, SD 0.58). At baseline, no differences in psychopathology between respondents and non-respondents were observed;16 also during follow-up no differences in psychopathology between those retained and those who dropped out were found 18. More detailed information about design, sample, procedures and non-response analysis of the TRAILS study can be found elsewhere 16 17.…”
Section: Methodsmentioning
confidence: 99%
“…Our sample consisted of participants who were slightly more at risk in comparison to the general population, but the variation was still within a normal range. However, this oversampling may have provided us with a more representative general population sample, as individuals with more antisocial behavior were more likely to drop-out from the TRAILS study (Huisman et al, 2008;Nederhof et al, 2012). Moreover, childhood adversities were assessed retrospectively.…”
Section: Limitationsmentioning
confidence: 99%
“…Detailed information about sample selection and analysis of non-response bias are reported elsewhere (de Winter et al, 2005;Nederhof et al, 2012). The current study used data from the first three measurement waves, to December 2007 (wave 3).…”
Section: Participantsmentioning
confidence: 99%
“…Cohort members were assessed at baseline when aged 11 years (n=2230) and then at ages 13 (n=2149), 16 (n=1816) and 19 years (n=1881). The retention rate over the 8-year follow-up period was 84.3% which is high for longitudinal studies of psychiatric outcomes (Nederhof et al, 2012). The flow chart of this study is illustrated in Figure 1.…”
Section: Trails Cohortmentioning
confidence: 99%
“…Behavioral assessments were undertaken at age 11, 13 and 16 years and formal lifetime psychiatric diagnoses were ascertained at age 19 years according to the TRAILS data collection protocol. Details of the TRAILS design, sampling and weighted prevalence rates of psychiatric disorders have already been published (Nederhof et al, 2012;Oldehinkel et al, 2015;Ormel et al, 2012;Ormel et al, 2015) and are summarised in the supplemental material.…”
Section: Trails Cohortmentioning
confidence: 99%